2018
DOI: 10.1007/s40430-018-1050-7
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent channel flow perturbed by triangular ripples

Abstract: This paper presents an experimental investigation of the perturbation of a turbulent closed-conduit flow by two-dimensional triangular ripples. Two ripple configurations were employed: one single asymmetric triangular ripple, and two consecutive asymmetric triangular ripples, all of them with the same geometry. Different water flows were imposed over either one or two ripples fixed to the bottom wall of a closed conduit, and the flow field was measured by PIV (particle image velocimetry). Reynolds numbers base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…The layout of the experimental device, a photograph of the test section, and microscopy images of the used grains are shown in the supporting information. (Alvarez & Franklin, 2018;Cúñez et al, 2018;Franklin et al, 2014) and found to follow the Blasius correlation (Schlichting, 2000), being within 0.0133 and 0.0202 m/s. By considering the fluid velocities applied to each grain type, the Shields number, = ( u 2 * )∕(( s − )gd), varied within 0.019 and 0.106, where g is the acceleration of gravity (see the supporting information for a description of the PIV tests, estimated deviations in u * and , and lists of all tested conditions).…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…The layout of the experimental device, a photograph of the test section, and microscopy images of the used grains are shown in the supporting information. (Alvarez & Franklin, 2018;Cúñez et al, 2018;Franklin et al, 2014) and found to follow the Blasius correlation (Schlichting, 2000), being within 0.0133 and 0.0202 m/s. By considering the fluid velocities applied to each grain type, the Shields number, = ( u 2 * )∕(( s − )gd), varied within 0.019 and 0.106, where g is the acceleration of gravity (see the supporting information for a description of the PIV tests, estimated deviations in u * and , and lists of all tested conditions).…”
Section: Methodsmentioning
confidence: 89%
“…The cross‐sectional mean velocities of water, U , varied between 0.226 and 0.365 m/s, corresponding to Reynolds numbers based on the channel height, Re = ρU 2 δ / μ , within 1.13 × 10 4 and 1.82 × 10 4 , where μ is the dynamic viscosity and ρ the density of the fluid. The shear velocities on the channel walls (base state), u ∗ , were computed based on measurements with a two‐dimensional particle image velocimetry (2D‐PIV) device (Alvarez & Franklin, 2018; Cúñez et al, 2018; Franklin et al, 2014) and found to follow the Blasius correlation (Schlichting, 2000), being within 0.0133 and 0.0202 m/s. By considering the fluid velocities applied to each grain type, the Shields number, θ=false(ρu2false)false/false(false(ρsρfalse)gdfalse), varied within 0.019 and 0.106, where g is the acceleration of gravity (see the supporting information for a description of the PIV tests, estimated deviations in u ∗ and θ , and lists of all tested conditions).…”
Section: Methodsmentioning
confidence: 99%
“…By computing an average over the whole barchan, we found that the average displacement of grains varies within 30 and 60 grain diameters, which is three to five times higher than displacements obtained over liquid-sheared plane beds by Lajeunesse et al [19] and Penteado and Franklin [20]. One possible explanation for higher values over the barchan dune is the presence higher turbulent stresses over the upwind face of barchans, as proposed by Wiggs et al [29] and measured by Cúñez et al [30], that would be responsible for the longer distances traveled by grains, but this rests to be investigated further. We found that the average velocity varies within 10 and 20 % of the cross-sectional mean velocity of the fluid and 30 and 60 % of the velocity based on the mean shear at the grain scale.…”
Section: Discussionmentioning
confidence: 42%
“…Considering that the threshold Shields θ c is higher over the dune positive slope and that the comparison is made for the same range of Shields values, the longer displacements over the barchan dune indicates that details of the structure of the water flow over the dune affect substantially bed load characteristics. It has been proposed that the curvature of streamlines induce higher turbulent stresses at low regions of the boundary layer close to the dune leading edge and smaller ones at low regions close to the dune crest (first proposed by Wiggs et al [29] and afterward measured experimentally, for example, for 2D dunes by Cúñez et al [30]). The higher turbulent stresses over the upwind face of barchans would then be responsible for the longer distances traveled by grains, but this rests to be investigated further.…”
Section: Lagrangian Frameworkmentioning
confidence: 99%
“…The cross-sectional mean velocities of water U were within 0.226 m/s and 0.312 m/s, corresponding to Reynolds numbers based on the channel height (Panton, 2010), Re = ρU2δ/μ, within 1.13 × 10 4 and 1.55 × 10 4 , respectively, and to Stokes numbers (Andreotti et al, 2013) St t = Udρ s /(18μ) within 6.3 and 35.5, where ρ is the density and μ the dynamic viscosity of the fluid. The shear velocities on the channel walls u * (base flow) were computed from velocity profiles measured in previous works with a two-dimensional particle image velocimetry device (Alvarez & Franklin, 2018;Cúñez et al, 2018;Franklin et al, 2014), and were found to follow the Blasius correlation (Schlichting, 2000), from which we found 0.0133 m/s ≤ u * ≤ 0.0168 m/s. This corresponds to Reynolds numbers at the grain scale, Re * = ρu * d/μ, within 3 and 8 and to Shields numbers, θ = 𝐴𝐴 ( 𝜌𝜌𝜌𝜌 2 * ) ∕((𝜌𝜌𝑠𝑠 − 𝜌𝜌)𝑔𝑔𝑔𝑔) , within 0.060 and 0.086.…”
Section: Methodsmentioning
confidence: 78%